The relationship of alcohol access in adolescence with omission learning and interneuron numbers - Lensing, Alicia (Kansas State University, 2023)
The typical autoshaping and omission contingency procedures consist of initially presenting a cue followed by a reward regardless of responding, a phase in which the subject usually learns to approach the cue (autoshaping), followed by presenting the same cue followed by reward only if the subject does not respond to the cue (omission contingency learning). Our lab has previously found that rats allowed to consume alcohol during adolescence show faster omission contingency learning later in adulthood. Here, we aim to determine neurobiological correlates relating to the behavioral differences in an autoshaping and omission contingency learning task and prior alcohol consumption in rats with or without prior alcohol access. A total of 24 male Long Evans rats were used and underwent the chronic intermittent access (CIA) alcohol exposure paradigm from postnatal days (PND) 26-68. After the end of CIA, rats began behavioral training in which they were trained on an autoshaping task for six days followed by omission contingency learning for six days. Animals were then sacrificed, and brains were stained for Parvalbumin (PV) and choline acetyltransferase (ChAT). Data were analyzed using both binomial and Poisson mixed effects models. Results showed that subjects exposed to alcohol did show faster omission contingency learning using the measure of number of lever presses made, but the measure of the likelihood to press the lever at least once during a trial failed to show this effect. For PV expressing (PV+) neurons there were no group differences between water and alcohol groups. For ChAT expressing (ChAT+) neurons there was a decrease in ChAT+ neurons in the alcohol group compared to the water group in Ch1/Ch2 cholinergic nuclei. There was also an increase in ChAT+ neurons in the alcohol group compared to the water group in the nucleus accumbens shell. However, there were positive correlations between the number of PV+ neurons in the DLS and ACC and levels of alcohol consumption in the alcohol group. There were also positive correlations between ChAT+ neurons in Ch1/Ch2, Ch3/Ch4, DMS, DLS, and nucleus accumbens core and levels of alcohol consumption in the alcohol group. These correlations showed that, as alcohol consumption in the alcohol group increased, the number of PV+ and ChAT+ neurons also increased in these brain areas. Since the majority of studies assessing the effects of alcohol on PV+ and ChAT+ neurons used forced exposure methods rather than voluntary methods, we were able to assess these correlations where most studies could not. These correlates are novel findings and further expand the scientific literature. Unfortunately, we did not find any differences in PV+ and ChAT+ neurons in the main brain areas believed to be involved in autoshaping and omission contingency (ACC, NAc Core, and DLS). Future research is needed for exploring the relationships between omission contingency learning and the brain areas that did show group differences and to assess the neuronal function within the brain areas associated with omission contingency learning.
Keywords: Omission contingency learning; Parvalbumin; Choline acetyltransferase; Adolescent alcohol exposure